2021
DOI: 10.1002/advs.202103646
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Efficient p‐Type Organic Thermoelectrics by Modulation of Acceptor Unit in Photovoltaic π‐Conjugated Copolymers

Abstract: 𝝅-Conjugated donor (D)−acceptor (A) copolymers have been extensivelystudied as organic photovoltaic (OPV) donors yet remain largely unexplored in organic thermoelectrics (OTEs) despite their outstanding mechanical bendability, solution processability and flexible molecular design. Importantly, they feature high Seebeck coefficient (S) that are desirable in room-temperature wearable application scenarios under small temperature gradients. In this work, the authors have systematically investigated a series of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…Great efforts have been given to synthesize alternative donor–acceptor (D–A) polymers because their high μ can contribute to the high electrical conductivity. , Despite lots of D–A polymers showing a high μ in OFET, only a few D–A polymers can be effectively doped by strong dopants . It has been reported that a polymer with a D–A backbone possesses a much lower doping efficiency due to the acceptor moiety being inactive for p-type doping. Unlike D–A polymers, thiophene polymers, such as poly­(3-hexylthiophene) (P3HT) and poly­(2,5-bis­(3-tetradecylthiophene-2-yl)­thieno­[3,2- b ]­thiophene) (PBTTT-C14), can be easily doped due to the matched energy levels to common dopants, but their electrical conductivity is limited due to the low intrinsic mobility. In general, the rigidity and coplanarity of conjugated units facilitate effective charge transport by increasing the probability for intermolecular π–π orbital overlap and thus interchain charge transport, leading to a high carrier mobility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Great efforts have been given to synthesize alternative donor–acceptor (D–A) polymers because their high μ can contribute to the high electrical conductivity. , Despite lots of D–A polymers showing a high μ in OFET, only a few D–A polymers can be effectively doped by strong dopants . It has been reported that a polymer with a D–A backbone possesses a much lower doping efficiency due to the acceptor moiety being inactive for p-type doping. Unlike D–A polymers, thiophene polymers, such as poly­(3-hexylthiophene) (P3HT) and poly­(2,5-bis­(3-tetradecylthiophene-2-yl)­thieno­[3,2- b ]­thiophene) (PBTTT-C14), can be easily doped due to the matched energy levels to common dopants, but their electrical conductivity is limited due to the low intrinsic mobility. In general, the rigidity and coplanarity of conjugated units facilitate effective charge transport by increasing the probability for intermolecular π–π orbital overlap and thus interchain charge transport, leading to a high carrier mobility.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Despite lots of D−A polymers showing a high μ in OFET, only a few D−A polymers can be effectively doped by strong dopants. 18 It has been reported that a polymer with a D−A backbone possesses a much lower doping efficiency due to the acceptor moiety being inactive for p-type doping. 18−20 Unlike D−A polymers, thiophene polymers, such as poly(3-hexylthiophene) (P3HT) and poly(2,5-bis(3-tetradecylthiophene-2-yl)thieno[3,2-b]thiophene) (PBTTT-C14), can be easily doped due to the matched energy levels to common dopants, 21−23 but their electrical conductivity is limited due to the low intrinsic mobility.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To explore more information of the solvent selection's effect in film morphology and the opto-electric property, we carried out the grazing incidence wide-angle X-ray scattering (GIWAXS) experiments. 42−48 49,50 Next, we utilized the space charge limited current (SCLC) method to see whether the charge mobility variation of active layers brought by different solvents follows the previous prediction. The hole and electron mobility (μ h and μ e ) evaluation are plotted in Figure S1, and the calculated results are given in Figure 1c and Table 1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These results indicate that the o-XY processed active layer has the fewest IP packings in a single domain but the largest number of OOP packings. Generally, the o-XY processed film should be the most favorable one in achieving efficient electron transport because the PBDB-T family polymers mainly contribute to the IP hole transport. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…[3,[8][9][10][11][12][13][14] Owing to the low κ of organic TE materials and the difficulty to measure correctly, the power factor (PF = α 2 σ) is often used to evaluate their TE performance. [9,[15][16][17][18] Recently, extensive studies on TE material design, fundamentals in charge generation/transport, and optimization of device architectures have been performed, successfully demonstrating a record high ZT up to 0.75 for poly(3,4-ethy lenedioxythiophene):polystyrene sulfonate (PEDOT:PSS)/ionic liquid (IL) heterostructures. [19] The enhancement of ZT is attributed to only a slight drop in σ and a significant rise in α due to ion accumulation of IL on the polymer surface which can scatter the low energy charge carriers and thus increase the mean energy of the holes at the cold side of the PEDOT:PSS films.To optimize the performance of organic TE generators (TEGs), high σ is the most important prerequisite.…”
mentioning
confidence: 99%